2003
DOI: 10.1086/375220
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Human Immunodeficiency Virus Infection on Recurrence of Tuberculosis after Rifampin-Based Treatment: An Analytical Review

Abstract: We reviewed 47 prospective studies of recurrence of pulmonary tuberculosis (TB) after cure to assess the influence of human immunodeficiency virus (HIV) infection and rifampin treatment. Multivariate regression revealed that the recurrence rate for HIV-uninfected persons increased with decreasing duration of therapy: it was 1.4 cases per 100 person-years for recipients of >or=7 months of rifampin therapy and 2.0 and 4.0 cases per 100 person-years for recipients of 5-6 and 2-3 months of rifampin therapy, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(122 citation statements)
references
References 42 publications
8
112
0
2
Order By: Relevance
“…Although the association of relapse with intermittent therapy is in line with recent publications (20,28), the importance of the duration of treatment in our study is not. A recent metaanalysis of prospective clinical trials reported no significant difference in risk of recurrence between HIV-infected patients who received 5 to 6 months of rifampin-based therapy and those who received 7 months or longer (29). This finding may reflect the fact that our study was a review of tuberculosis management outside the controlled context of a clinical trial.…”
Section: Discussionmentioning
confidence: 68%
“…Although the association of relapse with intermittent therapy is in line with recent publications (20,28), the importance of the duration of treatment in our study is not. A recent metaanalysis of prospective clinical trials reported no significant difference in risk of recurrence between HIV-infected patients who received 5 to 6 months of rifampin-based therapy and those who received 7 months or longer (29). This finding may reflect the fact that our study was a review of tuberculosis management outside the controlled context of a clinical trial.…”
Section: Discussionmentioning
confidence: 68%
“…Two studies which compared the use of RIF to the use of ethambutol (ETB) in the continuation phase after initial treatment with isoniazid (INH)-RIF-pyrazinamide (PZA)-ETB found that those on ETB-INH were 2 to 3 times more likely to experience treatment failure or TB relapse than those on RIF-INH for continuation therapy (135,204). Several meta-analyses have shown that treatment with a longer duration (6 months or longer) of a rifamycin drug (rifampin or rifabutin [RfB]) resulted in lower rates of failure and recurrence and improved survival during treatment, compared to only 2 months of treatment with a rifamycin drug (146,150,186). More recent data suggest that a duration of rifampin treatment even longer than the recommended 6 months may decrease failure and recurrence rates even further (146,239).…”
Section: Treatment Of Tb For Hiv-infected Patients: Rifampin Combinatmentioning
confidence: 99%
“…From the mid-1980s, tuberculosis programmes in countries with high prevalence of HIV infection, particularly in sub-Saharan Africa, faced increasing challenges: rising tuberculosis case notifi cations; disproportionally more patients with smear-negative disease 6 and drug-related side-eff ects; 7 high case fatality; 8 high rates of tuberculosis recurrence; 9 and increased transmission of M tuberculosis within congregate settings. In industrialised countries in the 1990s, outbreaks of multidrug-resistant (MDR) tuberculosis occurred in HIV-infected people in health facilities, 10 only to be re-enacted in the well publicised outbreak of extensively drug-resistant (XDR) tuberculosis in HIVinfected people in Tugela Ferry, KwaZulu Natal, South Africa, in 2005-06.…”
Section: The Interim Policy On Collaborative Tuberculosis and Hiv Actmentioning
confidence: 99%